Clinical Symptom Differences Between Mild and Severe COVID-19 Patients in China: A Meta-Analysis - He, Xiaobo; Cheng, Xiao; Feng, Xudong; Wan, Hong; Chen, Sihan; Xiong, Maoming (Frontiers in Public Health, 2021)
Abstract Objective The prognosis of mild and severe patients exists significant differences during the prevalence of COVID-19, and it will be significant to identify patients’ potential risk of progressing to severe cases according to their early clinical presentations. Therefore, we aim to systematically review the clinical symptoms of COVID-19 epidemic. Methods We searched PubMed, EMBASE, Web of Science, and CNKI (Chinese Database) for studies about the clinical features of COVID-19 in China from 18 March to 18 April. Then, REVMAN 5.3 software was used to conduct a meta-analysis. Results After screening, 20 articles including 3326 COVID-19 confirmed cases were selected from 142 articles we retrieved at the beginning of our research. We divided all the cases into severe group (including severe and critical severe patients) and mild group according to the "Diagnosis and Treatment Protocol for Novel Coronavirus Infection-Induced Pneumonia version 4 (trial)". Of all the initial symptoms (including fever, cough, abdominal pain, anorexia, chest tightness, diarrhea, dyspnea, expectoration, fatigue, headache, hemoptysis, myalgia, nausea or vomiting and pharyngalgia ) we studied, we found that cough (odds ratio [OR]=1.44, 95% confidence interval [CI]: 1.19-1.73; P < 0.001), fever (odds ratio [OR]=1.50, 95% confidence interval [CI]: 1.19-1.90; P < 0.001), dyspnea (odds ratio [OR]=6.18, 95% confidence interval [CI]: 3.59-10.64; P < 0.001), diarrhea (odds ratio [OR]=2.55, 95% confidence interval [CI]: 1.32-4.92; P < 0.001), fatigue (odds ratio [OR]=2.08, 95% confidence interval [CI]: 1.32-3.27; P < 0.01), expectoration (odds ratio [OR]=1.74, 95% confidence interval [CI]: 1.15-2.63; P < 0.01), myalgia (odds ratio [OR]=1.61, 95% confidence interval [CI]: 0.84-3.07; P < 0.001), hemoptysis (odds ratio [OR]=4.04, 95% confidence interval [CI]: 1.45-11.27; P < 0.001), abdominal pain (odds ratio [OR]=7.49, 95% confidence interval [CI]: 2.39-23.44; P < 0.001) and anorexia (odds ratio [OR]=2.79, 95% confidence interval [CI]: 1.52-5.11; P < 0.001) had significantly different distribution in two groups and was statistically significant (p<0.05). Conclusion Severe COVID-19 patients whose initial manifestation is dyspnea, hemoptysis, anorexia, diarrhea or fatigue especially abdominal pain should be closely monitored to prevent disease deterioration.